Effectiveness of Monitoring and Evaluation in Enhancing the Quality of Nursing Care Documentation in Inpatient - Baskoro Abdiansyah; Rr Tutik Sri Hariyati; Andi Amalia Wildani; Tuti Afriani; Sudaryati Sudaryati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Effective nursing care documentation is a fundamental component of improving service quality, ensuring patient safety, and supporting professional accountability. This study aimed to evaluate the effectiveness of monitoring and evaluation in enhancing the quality of nursing documentation in an inpatient ward of a hospital in South Jakarta. This pilot study employed a management function framework, with activities conducted through planning, organizing, implementing, and controlling phases. Monitoring and evaluation interventions using digital tools were carried out by head nurses and primary nurses for 10 staff nurses. This study used a total sampling technique involving 10 nurses, with data analyzed through descriptive quantitative and qualitative methods to compare pre- and post-feedback documentation quality and identify factors influencing monitoring and evaluation effectiveness. The results showed an increase of 40.7% in the average documentation score after monitoring-evaluation feedback was provided. Significant improvements were found in the areas of nursing diagnoses and interventions. Structured monitoring and direct feedback were effective in improving documentation consistency and accuracy. Monitoring and evaluation should be institutionalized as a routine program supported by standard operating procedures, continuous training, and supervision to ensure the sustainability of high-quality nursing documentation.